The Pacified Face: Early Embodiment Processes and the Use of Dummies - Rychlowska, Magdalena; Vanderwert, Ross (Frontiers in Psychology, 2020)
Few things affect us as much as facial expressions, as they inform us about others’ feelings and intentions, thereby influencing our own emotions and behaviors. A substantial body of literature links the critical abilities of recognizing and understanding emotion displays with facial mimicry, a sensorimotor process involving rapid imitation of perceived expressions. For example, blocking or altering facial mimicry in adults leads to disruptions in judgments in emotion recognition or emotional language processing. The present review focuses on pacifier use in infancy, a common practice that has the potential to interfere with infants’ facial movements in ways identical to laboratory paradigms designed to block facial mimicry. Despite this similarity and the widespread use of infant soothers, little is known about their long-term effects. Here we review studies exploring the psychological correlates and implications of pacifier use. In particular, we discuss how soothers may interfere with the development of sensorimotor simulation in infants and present evidence linking pacifier use with disrupted adults’ mimicry of facial expressions displayed by infants. Other preliminary findings reveal negative correlations between the use of soothers and children’s spontaneous facial mimicry as well as emotional competence of young adults. Such studies, although correlational, suggest that this widespread parenting practice may affect the development of social skills grounded in sensorimotor processes. We discuss the implications of these findings and propose avenues for future research that can provide insights into the role of embodied processes in the development of emotional competence and adult functioning.